Menumbuhkan Karakter Tanggung Jawab Melalui Buku Ajar Tematik Integratif Berbasis Karakter - Syabrina, Muhammad (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2017)
Teaching not only convey the content of the subject matter, but also interpreted as the process of character formation. At elementary school level learners need model more than cleverness. Growing the character of responsibilities can be done by teachers in several ways, one of them using textbooks integrative thematic teaching based on character. This textbook is structured on the basis of competence that is combined with the content of responsibility characters. This textbook is designed with interesting, simple and easily understood by student, as well as stimulate learners to utilize textbook as the main learning resource. Through the content of characters packed in the form of materials and learning activities in textbooks, the character of student responsibility will be formed because they experience themselves and do it in everyday life.